Genetic dissection of protein and starch during wheat grain development using QTL mapping and GWAS - Guo, Yingxin; Wang, Guanying; Guo, Xin; Chi, Songqi; Yu, Hui; Jin, Kaituo; Huang, Heting; Wang, Dehua; Wu, Chongning; Tian, Jichun; Chen, Jiansheng; Bao, Yinguang; et al. (Frontiers in Plant Science, 2023)
Protein, starch and their components are important for wheat grain yield and end-products, which are affected by grain development. Therefore, QTL mapping and a genome-wide association study (GWAS) of grain protein content (GPC), glutenin macropolymer content (GMP), amylopectin content (GApC) and amylose content (GAsC) were performed at 7, 14, 21 and 28 days after anthesis (DAA) in two environments using a recombinant inbred line (RIL) population of 256 stable lines and a panel of 205 wheat accessions. A total of 29 unconditional QTLs, 13 conditional QTLs, 99 unconditional marker‒trait associations (MTAs) and 14 conditional MTAs significantly associated (P<10-4) with four traits were found on fifteen chromosomes, with 5.35% to 39.86% of phenotypic variation explained (PVE). Three major QTLs (QGPC3B, QGPC2A and QGPC(S3|S2)3B) and SNP clusters on the 3A and 6B chromosomes were detected for GPC, and the SNP TA005876-0602 was stably expressed during the three periods in the natural population. The QGMP3B locus was detected five times in three developmental stages in two environments with 5.89%-33.62% PVE, and SNP clusters for GMP content were found on the 3A and 3B chromosomes. For GApC, the QGApC3B.1 locus had the highest PVE of 25.69%, and SNP clusters were found on chromosomes 4A, 4B, 5B, 6B and 7B. Four major QTLs of GAsC were detected at 21 and 28 DAA. Most interestingly, both QTL mapping and GWAS analysis indicated that four chromosomes (3B, 4A, 6B and 7A) were mainly involved in the development of protein and starch synthesis. Of these, the wPt-5870-wPt-3620 marker interval on chromosome 3B seemed important because it played an important role in the synthesis of GMP and amylopectin before 7 DAA, protein and GMP from 14 to 21 DAA, and GApC and GAsC from 21 to 28 DAA. There were twenty-eight and sixty-nine candidate genes predicted for major loci from QTL mapping and GWAS, respectively, in the Chinese Spring IWGSC RefSeq v1.1 genome assembly. Most of them have multiple effects on protein and starch synthesis during grain development. These results provide new insights and information for the potential regulatory network between grain protein and starch synthesis.